Interior film

By using a combined structure of polyethylene terephthalate resin substrate, ultraviolet curing imprint layer, metal layer and resin base layer in the interior film, the high moldability products of the interior film in the prior art are solved. The problem of poor moldability is achieved by high design freedom and excellent moldability.

CN115873287BActive Publication Date: 2025-01-03KCC GLASS CORP
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202210767726.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2021-09-27
Filing Date
2022-06-30
Publication Date
2025-01-03
Estimated Expiration
2042-06-30

AI Technical Summary

Technical Problem

Interior films manufactured by existing UV curing processes are prone to cracks or film peeling in highly moldable products, making it difficult to achieve design freedom and excellent moldability.

Method used

The interior film structure is adopted including a base material layer, more than one imprinted layer, more than one metal layer and base layer. The base material layer is made of polyethylene terephthalate resin, and the imprinted layer is made of ultraviolet curing type. The composition is formed, the metal layer is prepared by deposition or printing technology, and the base layer is composed of resin and curing agent, which improves the adhesion and moldability of the film through specific laminated structures and material ratios.

Benefits of technology

It realizes an interior film with high design freedom and excellent moldability, and is suitable for high moldability products such as washing machines and dryers, reducing the incidence of film peeling and cracks, and improving the adhesion and processability of the film.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0003722811010000091
    Figure BDA0003722811010000091
  • Figure BDA0003722811010000101
    Figure BDA0003722811010000101
  • Figure BDA0003722811010000121
    Figure BDA0003722811010000121
Patent Text Reader

Abstract

The present invention relates to an interior film having a high degree of design freedom and excellent formability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to an interior film having a high degree of design freedom and excellent formability. Background Art

[0002] In order to show the metallic texture on vehicle interior and exterior parts, building materials, home appliance housings, etc., methods such as metal plating and metal painting are used on the surface of the substrate. However, metal plating or painting not only has a complicated process and a low yield, but also generates wastewater and volatile organic compounds during the process, thus posing an environmental problem.

[0003] In order to solve these problems, a method of laminating an interior film having a metallic texture on the surface of a substrate has recently been used. In order to produce an interior film that can specifically realize a design pattern, various coating methods have been proposed, and printing type, galaxy type, metal type, etc. have been applied. However, these methods have disadvantages such as difficulty in realizing various designs, so recently, interior film products manufactured by UV curing process methods (imprinting) using UV curing compositions to form patterns have been actively developed.

[0004] As an example, Korean Patent Publication No. 10-2011-0136437 discloses a film for interior decoration with a metallic texture, which is composed of a UV embossed layer formed on one surface of a polyethylene terephthalate film, a metal deposition layer formed on the other surface of the polyethylene terephthalate film, an adhesive layer formed on the metal deposition layer, and a colored film layer. However, in the case of a film manufactured by an existing UV curing process, although the metallic texture of the appearance and the freedom of pattern formation are excellent, when it is applied to products (washing machines, dryers, films, etc.) that require high formability such as deep drawing, there is a problem of poor formability such as cracks or film peeling. Therefore, it is necessary to develop an interior film with high design freedom and excellent formability. Summary of the invention

[0005] (Problems to be solved by the invention)

[0006] The present invention provides an interior film having a high degree of design freedom and excellent formability.

[0007] (Measures taken to solve the problem)

[0008] The invention provides an interior film comprising a substrate layer, one or more embossing layers, one or more metal layers and a primer layer.

[0009] (Effects of the Invention)

[0010] The present invention provides an interior film having high design freedom and excellent formability. The interior film of the present invention can be applied to products (washing machines, dryers, films, etc.) that require high formability such as deep drawing. DETAILED DESCRIPTION

[0011] Hereinafter, the present invention will be described in detail. However, the present invention is not limited to the following contents, and each component can be variously deformed or selectively mixed and used as required. Therefore, it should be understood that all changes, equivalents or substitutes included in the thought and technical scope of the present invention are included.

[0012] The "elongation" used in this specification is measured by conventional methods known in the art. For example, a test piece formed into a dog bone, a rod or a dumbbell shape can be used and the elongation can be measured by a universal testing machine (UTM). The "glass transition temperature" is measured by conventional methods known in the art. For example, it can be measured by differential scanning calorimetry (DSC). The "weight average molecular weight" and "number average molecular weight" are measured by conventional methods known in the art. For example, they can be measured by GPC (gel permeation chromatograph) method. Functional group values ​​such as "hydroxyl value" are measured by conventional methods known in the art. For example, it can be measured by titration method.

[0013] The interior film of the present invention comprises a substrate layer, one or more imprint layers, one or more metal layers and a primer layer.

[0014] Base material layer

[0015] The interior film according to the present invention includes a base material layer. The base material layer functions as a support body of the interior film.

[0016] The substrate is made of a resin including polyethylene terephthalate (PET), in which case the processability of the interior film can be improved. The resin constituting the substrate may further include a thermoplastic resin used in the art in addition to polyethylene terephthalate (PET). As the thermoplastic resin, polyethylene terephthalate glycol resin (PETG resin), nylon, polybutylene terephthalate resin (PBT resin), acrylonitrile-butadiene-styrene resin (ABS resin), acrylonitrile-styrene-acrylate resin, acrylic resin, polyolefin resin, polycarbonate resin, vinyl chloride resin, etc. can be used, and they can be used alone or in combination of two or more.

[0017] As an example, the longitudinal and transverse tensile strengths of the resin constituting the above substrate are 10 to 35 kgf / mm 2 , for example, it can be 18 to 25 kgf / mm 2 The longitudinal elongation is 180 to 300%, for example, 180 to 250%, the transverse elongation is 160 to 300%, for example, 160 to 210%, and the glass transition temperature is 40 to 110°C, for example, 60 to 90°C.

[0018] When the longitudinal and transverse tensile strengths of the resin constituting the above-mentioned substrate are less than the above-mentioned range, the film strength becomes weak, and thus the film breaks due to the molding pressure, and the molding processing properties are reduced. When the film strength exceeds the above-mentioned range, the film strength becomes strong, and the film peeling occurs, and the molding processing properties are reduced. When molding interior films for home appliances, etc., peeling occurs at the portion with relatively poor adhesion due to the pressure (stress) applied to the film. When the elongation of the resin constituting the above-mentioned substrate is within the above-mentioned range, the pressure applied to other layers is reduced, thereby reducing the possibility of film peeling.

[0019] When the longitudinal and transverse elongation of the resin constituting the above-mentioned substrate is less than the above-mentioned range, the elongation property of the film deteriorates, and the film breaks and peels off during the molding process, and the processing properties are reduced. When it exceeds the above-mentioned range, the film smoothness, heat shrinkage and other workability and the film properties such as pencil hardness are reduced. The glass transition temperature is correlated with the tensile strength and elongation. When it deviates from the above-mentioned range, the film peels off and breaks during processing, which may cause problems.

[0020] The surface (one or both surfaces) of the substrate may be treated with one or more of acrylic resins and urethane resins. The surface treatment method of acrylic resins or urethane resins is not particularly limited, and conventional methods used in the art may be used. As an example, an acrylic resin or urethane resin composition may be coated on the substrate surface to a thickness of tens to hundreds of nm. As the coating method, methods such as gravure, micro gravure, reverse, and slit die coating may be used.

[0021] As an example, polyethylene terephthalate treated with a urethane resin can be used as the substrate. When the surface of polyethylene terephthalate is treated with a urethane resin, the surface of the polyethylene terephthalate is made uneven to increase the contact area, thereby increasing the surface tension and improving the adhesion of the substrate layer. Therefore, the adhesion to the ultraviolet curable composition is improved, thereby ensuring excellent pattern formability, and as a result, it is possible to provide an interior film with excellent formability and design.

[0022] The thickness of the substrate layer can be appropriately set according to the purpose of the interior film, for example, 20 to 500 μm, as another example, 25 to 150 μm, as another example, 25 to 100 μm. When the thickness of the substrate layer satisfies the above range, the interior film can be given excellent formability and designability.

[0023] Embossed layer

[0024] The interior film according to the present invention includes an embossed layer, which can realize 3D stereoscopic effects and pattern design on the interior film, improve adhesion, scratch resistance, weather resistance, crack resistance, etc., and play a role in controlling gloss.

[0025] The embossing layer is formed of an ultraviolet curable composition. As an example, the ultraviolet curable composition is an ultraviolet curable polyurethane acrylate composition, which includes a urethane (meth)acrylate oligomer, a (meth)acrylate monomer, and a photoinitiator.

[0026] The urethane (meth)acrylate oligomer is a main component for forming the coating film, and plays a role in controlling the crosslinking density of the entire coating film to thereby exhibit strength, durability, and adhesion in the coating film.

[0027] The glass transition temperature of the above-mentioned urethane (meth) acrylate oligomer is 10 to 50°C, for example, 20 to 40°C, and the weight average molecular weight is 5,000 to 20,000 g / mol, for example, 10,000 to 15,000 g / mol. When the glass transition temperature of the urethane (meth) acrylate oligomer falls within the above-mentioned range, the coating film maintains sufficient hardness, thereby preventing damage or peeling due to external impact, and can prevent the coating film from becoming too hard and cracking during post-processing. In addition, when the weight average molecular weight falls within the above-mentioned range, excellent reactivity and heat resistance can be shown.

[0028] The content of the urethane (meth) acrylate oligomer is 15 to 50% by weight, for example, 20 to 30% by weight, based on the total weight of the ultraviolet curable composition. When the content of the urethane (meth) acrylate oligomer is less than the above-mentioned range, the overall physical properties such as adhesion, chemical resistance, hardness, and flexibility will be reduced. When the content exceeds the above-mentioned range, the viscosity will increase, thereby deteriorating the workability.

[0029] The (meth)acrylate monomer functions as a crosslinking agent for adjusting the crosslink density between polymer molecules, and also plays an auxiliary role in imparting hardness, adhesion, appearance characteristics, workability, etc. to the coating film.

[0030] As the (meth)acrylate monomer, trimethylolpropane triacrylate (TMPTA), trimethylolpropane trimethacrylate (TMPTMA), trimethylolpropane ethoxy triacrylate (TMPEOTA), pentaerythritol triacrylate (PETA), glyceryl propoxylated triacrylate (GPTA), pentaerythritol tetraacrylate (PETTA), dipentaerythritol pentaacrylate (DPPA), dipentaerythritol hexaacrylate (DPHA), 1,6-hexanediol diacrylate (HDDA), 1,6-hexanediol dimethacrylate (HDDMA), butanediol diacrylate (BDDA), tripropylene glycol diacrylate (TPPA), and the like can be used. The invention also includes the following: polyoxyethylene glycol diacrylate (POGDA), triethylene glycol diacrylate (TEGDA), neopentyl glycol diacrylate (NPGDA), polyethylene glycol 400 diacrylate (PEG400DA), polyethylene glycol 200 diacrylate (PEG200DA), dipropylene glycol diacrylate (DPGDA), tetraethylene glycol diacrylate (TTEGDA), tetraethylene glycol dimethacrylate (TTEGDMA), 9-ethylene glycol diacrylate (9-EGDA), triethylene glycol dimethacrylate (TEGDMA), isobornyl (meth)acrylate (IBOA), acryloyl morpholine (ACMO), etc., which can be used alone or in combination of two or more.

[0031] The content of the (meth)acrylate monomer is 30 to 75% by weight, for example, 40 to 70% by weight, based on the total weight of the UV curable composition. When the content of the (meth)acrylate monomer is less than the above-mentioned range, the viscosity increases, so the workability decreases. When it exceeds the above-mentioned range, the oligomer content decreases relatively, so the chemical resistance decreases.

[0032] The photoinitiator is a component that initiates photopolymerization by being excited by ultraviolet light (UV) or the like, and any photoinitiator commonly used in the art can be used without limitation. For example, Irgacure 184, Irgacure 369, Irgacure 651, Irgacure 819, Irgacure 907, benzoin alkyl ether, benzophenone, benzoin dimethyl katal, hydroxycyclohexyl phenylacetone, chloroacetophenone, 1,1-dichloroacetophenone, diethoxyacetophenone, hydroxyacetophenone, 2-chlorothioxanthone, 1,1-dichloroacetophen ... thioxanthone), 2-ETAQ (2-EthylAnthraquinone, 2-ethylanthraquinone), 1-Hydroxy-cyclohexyl-phenyl-ketone, 2-Hydroxy-2-methyl-1-phenyl-1-propanone, 2-Hydroxy-1-[4-(2-hydroxyethoxy)phenyl]-2-methyl-1-propanone, methylbenzoylformate, etc., and these can be used alone or in combination of two or more.

[0033] The content of the photoinitiator may be 1 to 5% by weight based on the total weight of the ultraviolet curable composition. When the content of the photoinitiator falls within the above range, the photopolymerization reaction can be sufficiently carried out without deteriorating the physical properties of the coating film.

[0034] The thickness of the embossed layer is 1 to 100 μm, for example, 3 to 30 μm. When the thickness of the embossed layer satisfies the above range, the pattern of the interior film is realized with excellent pattern visibility, surface hardness, processability, etc., and ultraviolet rays can be uniformly irradiated, thereby achieving uniform curing.

[0035] The interior film of the present invention may include more than one embossed layer. As an example, the embossed layer may be laminated on the upper surface or the lower surface or the upper surface and the lower surface of the substrate layer. The embossed layer located on the upper surface of the substrate specifically realizes the 3D stereoscopic effect and pattern design in the interior film, improves the surface hardness, processability, etc., and plays a role in controlling the gloss. The embossed layer located on the lower surface of the substrate plays a role in improving the adhesion with the metal layer in addition to the above functions.

[0036] Metal layer

[0037] The interior film according to the present invention includes a metal layer, which imparts a variety of colors or metallic effects such as metallic colors or textures to the interior film and plays a role in improving surface brightness and hiding power.

[0038] The metal layer may be a metal deposition layer or a metal printing layer.

[0039] The metal deposition layer is formed by depositing one or more metals selected from the group consisting of aluminum, chromium, nickel, stainless steel (SUS), copper, silver, gold, platinum, etc. As a deposition method, vacuum thermal deposition, sputtering deposition, etc. can be used.

[0040] The metal print layer is formed of a composition including a binder resin and a metal pigment.

[0041] The binder resin plays a role in enhancing the weather resistance of the interior sheet. As the binder resin, vinyl copolymers, chlorinated polypropylene (CPP), acrylic resins, urethane resins, polyamides, nitrocellulose, cellulose acetate butyrate, etc. can be used, and they can be used alone or in combination of two or more.

[0042] As an example, the glass transition temperature of the binder resin is 30 to 100° C., such as 50 to 80° C., and the weight average molecular weight is 150,000 to 500,000 g / mol, such as 250,000 to 300,000 g / mol. When the binder resin is used, the interior film can be provided with excellent processability and heat resistance.

[0043] The content of the binder resin is 75 to 98 weight percent, for example, 85 to 95 weight percent, based on the total weight of the composition forming the metal printing layer. If the content of the binder resin is less than the above range, the adhesive force will be reduced, and if it exceeds the above range, the metallic property will be reduced.

[0044] The metal pigment may be one or more metals selected from the group consisting of aluminum, chromium, nickel, stainless steel (SUS), copper, silver, gold, platinum, and the like.

[0045] The composition forming the metal printing layer may further include a colored pigment in addition to the metal pigment. As the colored pigment, organic pigments, inorganic pigments, etc. commonly used in the art may be used without limitation, and they may be used alone or in combination of two or more. Non-limiting examples of the colored pigments that can be used include azo, phthalocyanine, iron oxide, cobalt, carbonate, sulfate, silicate, chromate pigments, etc., for example, titanium dioxide, zinc oxide, bismuth vanadate, cyanine green, carbon black, iron oxide red, iron oxide yellow, navy blue, cyanine blue, and mixtures of two or more thereof.

[0046] The composition for forming the metal printing layer may further include a solvent. The solvent facilitates the coating operation and plays a role in ensuring the smoothness and appearance of the coating film by adjusting the volatilization rate of the solvent.

[0047] As the above-mentioned solvent, there can be used aromatic hydrocarbon solvents such as toluene and xylene; ketone solvents such as methyl ethyl ketone, methyl propyl ketone, methyl butyl ketone, ethyl propyl ketone, methyl isobutyl ketone, methyl aryl ketone, and diisobutyl ketone; ester solvents such as methyl acetate, ethyl acetate, n-propyl acetate, isopropyl acetate, isopropyl acetate, butyl acetate, methyl cellosolve acetate, cellosolve acetate, butyl cellosolve acetate, and carbitol acetate; or alcohol solvents such as n-propanol, isopropanol, n-butanol, isobutanol, and tert-butanol.

[0048] The content of the solvent may be 1 to 40% by weight based on the total weight of the composition forming the metal printing layer. If the content of the solvent is less than the above range, the effect of improving the workability of coating is small, and if the content of the solvent exceeds the above range, the workability of coating may be problematic because the appropriate viscosity cannot be maintained.

[0049] The interior film of the present invention may include more than one metal layer. As an example, the metal layer may be laminated on the lower surface of the substrate layer, the lower surface of the embossed layer, or the lower surface of the substrate layer and the lower surface of the embossed layer. The metal layer may be composed of two or more layers. Compared with a single layer, even if a metal layer of the same thickness is formed, when multiple layers are laminated, better metallic properties can be specifically achieved with a small amount of metal.

[0050] The thickness of the metal layer may be 0.1 to 10 μm. If the thickness of the metal layer is less than 0.1 μm, the color or metallic property may not be fully realized, and if the thickness exceeds 10 μm, the aesthetics, surface appearance, workability, etc. may be reduced.

[0051] Basal layer

[0052] The interior film according to the present invention includes a base layer, which imparts heat resistance and interlayer adhesion to the interior film and, together with the substrate, improves the elongation and formability of the interior film.

[0053] The base layer is formed of a composition including a resin and a curing agent.

[0054] The resin includes polyester resin, epoxy resin, polyurethane resin, polyacrylic resin, polyolefin resin or a mixture thereof.

[0055] The weight average molecular weight of the above resin is 2,000 to 13,000 g / mol, for example, 4,000 to 10,000 g / mol, the glass transition temperature is 20 to 80°C, for example, 40 to 60°C, and the hydroxyl value is 10 to 50 mgKOH / g, for example, 20 to 30 mgKOH / g. In the case of using a resin having the weight average molecular weight and glass transition temperature range described above, excellent interlayer adhesion, heat resistance and processability can be shown. In the case where the weight average molecular weight and glass transition temperature are less than the range described above, the heat resistance will be reduced, and in the case of exceeding the range, it will become too hard, thereby reducing the processability.

[0056] The curing agent includes an isocyanate compound. For example, 2,4-toluene diisocyanate, 2,6-toluene diisocyanate, xylene-1,4-diisocyanate, xylene-1,3-diisocyanate, 4,4'-diphenylmethane diisocyanate, 2,4'-diphenylmethane diisocyanate, 2,2'-diphenylmethane diisocyanate, 4,4'-diphenylether diisocyanate, polymethylene polyphenylene polyisocyanate, 2-nitrodiphenyl-4,4'-diisocyanate, 2,2'-diphenylpropane-4,4'-diisocyanate, 3,3'-dimethyldiphenylmethane-4,4'-diisocyanate, 4,4'-diphenylpropane diisocyanate, m-phenylene diisocyanate, Aromatic isocyanates such as cyanate, p-phenylene diisocyanate, naphthalene-1,4-diisocyanate, naphthalene-1,5-diisocyanate, and 3,3'-dimethoxydiphenyl-4,4'-diisocyanate; aliphatic isocyanates such as 1,4-diisocyanatobutane, 1,5-diisocyanatopentane, 1,6-diisocyanatohexane (1,6-hexamethylene diisocyanate, HMDI), 1,6-diisocyanato-2,2,4-trimethylhexane, and 2,6-diisocyanatohexanoic acid methyl ester (lysine diisocyanate); and alicyclic diisocyanates such as isophorone diisocyanate, hydrogenated benzyl diisocyanate, and hydrogenated diphenylmethane diisocyanate.

[0057] As an example, with respect to the above-mentioned isocyanate compound, the NCO content is 10 to 30% by weight, for example, 20.5 to 21.9% by weight, the number average molecular weight is 300 to 2,500 g / mol, for example, 500 to 1,500 g / mol, and the weight average molecular weight is 500 to 4,000 g / mol, for example, 1,000 to 3,000 g / mol. In the case where the NCO content of the above-mentioned isocyanate compound is less than the aforementioned range, the curing rate is reduced, so the adhesion and heat resistance are reduced. In the case where the aforementioned range is exceeded, the uncured NCO remains, which may cause the water resistance to decrease or change over time. In addition, in the case where the number average molecular weight and the weight average molecular weight fall within the aforementioned range, excellent curing property and heat resistance can be shown.

[0058] The composition forming the above-mentioned base layer may further contain a solvent. As the above-mentioned solvent, aromatic hydrocarbon solvents such as toluene and xylene can be used; ketone solvents such as methyl ethyl ketone, methyl propyl ketone, methyl butyl ketone, ethyl propyl ketone, methyl isobutyl ketone, methyl aryl ketone, and diisobutyl ketone; ester solvents such as methyl acetate, ethyl acetate, n-propyl acetate, isopropyl acetate, isopropyl acetate, butyl acetate, methyl cellosolve acetate, cellosolve acetate, butyl cellosolve acetate, and carbitol acetate; or alcohol solvents such as n-propanol, isopropanol, n-butanol, isobutyl alcohol, and tert-butanol can be used.

[0059] The composition forming the base layer may further contain ink. In this case, color can be specifically realized on the interior film.

[0060] The ink contains a pigment and a binder resin. As the pigment, iron oxide, titanium oxide, carbon black, barium sulfate, calcium carbonate, kaolin, mica, aluminum, chromium oxide, cobalt aluminate, azo pigment, phthalocyanine pigment, anthraquinone pigment, etc. can be used, and they can be used alone or in combination of two or more. As the binder resin, vinyl chloride-vinyl acetate copolymer, acrylic resin, urethane resin, etc. can be used, and they can be used alone or in combination of two or more.

[0061] As an example, the composition forming the above-mentioned base layer may include 10 to 40% by weight of the above-mentioned resin and 3 to 10% by weight of the above-mentioned curing agent based on the total weight of the composition. In addition, the composition forming the above-mentioned base layer may further include 50 to 80% by weight of the above-mentioned solvent and 0 to 40% by weight of the above-mentioned ink based on the total weight of the composition.

[0062] The base layer may be stacked on the lower surface of the metal layer. When the metal layer is composed of two or more layers, the base layer may be stacked between the plurality of metal layers.

[0063] The thickness of the base layer may be 0.1 to 20 μm. If the thickness of the base layer is less than the above range, the main functions of the base, namely, the physical properties of adhesion and heat resistance, will be reduced. If it exceeds the range, there is a risk of poor workability such as poor drying.

[0064] The interior film of the present invention includes a substrate layer, one or more embossed layers, one or more metal layers and a base layer. As an example, the interior film of the present invention includes an embossed layer, a substrate layer, an embossed layer, a metal layer (single or multiple layers) and a base layer stacked in sequence from above. As another example, the interior film of the present invention includes an embossed layer, a substrate layer, a metal layer (single or multiple layers) and a base layer stacked in sequence from above. As yet another example, the interior film of the present invention includes a substrate layer, an embossed layer, a metal layer (single or multiple layers) and a base layer stacked in sequence from above.

[0065] The method for forming the interior film is not particularly limited, and a conventional method known in the art may be used.

[0066] As an example, the curable composition is applied on a substrate and then embossed to form an embossed layer, and a composition for forming a metal printing layer is applied using a gravure printer to form a single or multiple metal layers, and a transparent or ink-coated base layer is formed using a gravure printer according to the design, and then dried in an oven, and the above-mentioned interior film can be prepared in this way. As another example, the curable composition is applied on a substrate and then embossed to form an embossed layer, and a metal is deposited by sputtering deposition to form a single or multiple metal layers, and a transparent or ink-coated base layer is formed using a gravure printer according to the design, and then dried in an oven, and the above-mentioned interior film can be prepared in this way.

[0067] When preparing an interior film having a structure in which the embossed layers are laminated on the upper and lower surfaces of the substrate, two embossed layers can be simultaneously formed on the upper and lower surfaces of the substrate by double embossing.

[0068] Hereinafter, the present invention will be further specifically described by way of examples. However, the following examples are only provided to help understand the present invention, and the scope of the present invention is not limited to the examples in any sense.

[0069] [Experimental Example 1-16]

[0070] A first imprint layer (thickness of 6 μm) and a second imprint layer (thickness of 6 μm) were formed on the upper and lower surfaces of a substrate sheet by an imprinting process using an ultraviolet curing polyurethane acrylate coating. Afterwards, a metal layer was formed on the second imprint layer by a gravure printing process or a deposition process. Next, a base layer (wet coating thickness of 9 μm) was formed by a gravure printing process. By the above method, interior films of various experimental examples having a first imprint layer / base layer / second imprint layer / metal layer / base layer having the composition of Table 1 were prepared in sequence.

[0071]

Table 1

[0072]

[0073]

[0074] A-1: Polyethylene terephthalate (thickness 30 μm, longitudinal tensile strength 20 kgf / mm 2 , transverse tensile strength is 20kgf / mm 2 , longitudinal elongation of 190%, transverse elongation of 180%, Tg of 50°C, urethane resin surface treatment)

[0075] A-2: Polyethylene terephthalate (thickness 80 μm, longitudinal tensile strength 22 kgf / mm2 , transverse tensile strength is 19kgf / mm 2 , longitudinal elongation is 220%, transverse elongation is 167%, Tg is 70℃, urethane resin surface treatment)

[0076] A-3: Polyethylene terephthalate (thickness 50 μm, longitudinal tensile strength 25 kgf / mm 2 , transverse tensile strength is 25kgf / mm 2 , longitudinal elongation 200%, transverse elongation 200%, Tg 65℃, urethane resin surface treatment)

[0077] A-4: Polyethylene terephthalate (thickness 50 μm, longitudinal tensile strength 28 kgf / mm 2 , transverse tensile strength is 27kgf / mm 2 , longitudinal elongation of 160%, transverse elongation of 134%, Tg of 65°C, urethane resin surface treatment)

[0078] B-1: Urethane acrylate resin (glass transition temperature: 25°C, weight average molecular weight: 11,000 g / mol)

[0079] B-2: Urethane acrylate resin (glass transition temperature: 40°C, weight average molecular weight: 14,000 g / mol)

[0080] B-3: Urethane acrylate resin (glass transition temperature: 30°C, weight average molecular weight: 12,500 g / mol)

[0081] B-4: Urethane acrylate resin (glass transition temperature: 55°C, weight average molecular weight: 20,000 g / mol)

[0082] C-1: Urethane acrylate resin (glass transition temperature: 30°C, weight average molecular weight: 12,000 g / mol)

[0083] C-2: Urethane acrylate resin (glass transition temperature: 35°C, weight average molecular weight: 15,000 g / mol)

[0084] C-3: Urethane acrylate resin (glass transition temperature: 0°C, weight average molecular weight: 4,000 g / mol)

[0085] D-1: Metal printing layer (nitrocellulose resin (glass transition temperature of 70°C, weight average molecular weight of 270,000 g / mol) + aluminum)

[0086] D-2: Metal deposition layer (aluminum vacuum thermal deposition)

[0087] D-3: Metal deposition layer (nickel / chromium sputtering deposition)

[0088] E-1: polyester resin (weight average molecular weight 8,000 g / mol, glass transition temperature 55°C, hydroxyl value 30 mgKOH / g) + isocyanate compound (NCO content 21%, number average molecular weight 700 g / mol, weight average molecular weight 1,300 g / mol)

[0089] E-2: polyester resin (weight average molecular weight 3,000 g / mol, glass transition temperature 45°C, hydroxyl value 25 mgKOH / g) + isocyanate compound (NCO content 23%, number average molecular weight 1,000 g / mol, weight average molecular weight 1,900 g / mol)

[0090] E-3: polyester resin (weight average molecular weight of 10,000 g / mol, glass transition temperature of 42°C, hydroxyl value of 22 mgKOH / g) + isocyanate compound (NCO content of 22%, number average molecular weight of 1,300 g / mol, weight average molecular weight of 2,300 g / mol)

[0091] E-4: polyester resin (weight average molecular weight of 15,000 g / mol, glass transition temperature of 45°C, hydroxyl value of 55 mgKOH / g) + isocyanate compound (NCO content of 21%, number average molecular weight of 2,600 g / mol, weight average molecular weight of 4,700 g / mol)

[0092] [Physical property evaluation]

[0093] The physical properties of the interior film prepared in each experimental example were measured by the following methods, and the results are shown in Table 2 below.

[0094] Test piece production

[0095] After applying a 45 μm thick adhesive (FU2272, KCC) for steel plate lamination on a hot-dip galvanized steel plate (GI steel plate) with a thickness of 800 μm and baking it at a raw material temperature (peak material temperature (PMT)) of 232°C, the interior film prepared in each experimental example was bonded to the steel plate using a laminating roller to produce a test piece.

[0096] Processability (Erickson test)

[0097] After using a cutter to cut holes in the left, right, up and down directions (5 mm apart, in a tic-tac-toe pattern) on the interior film surface of each specimen, an Ericshen testing machine was used to test the film at 6 mm, 8 mm, and 10 mm, respectively, and the film was observed to see if it peeled off.

[0098] Hot water resistant

[0099] The interior film surface of each specimen was cut with a cutter along the left and right, up and down directions (5 mm intervals, in a tic-tac-toe shape), and after applying 6 mm, 8 mm, and 10 mm Erichsen processing, it was placed at 80°C and 98°C for 0.5 hours, and then the film was observed for any peeling.

[0100] UV Crack

[0101] The interior film surface of each test piece was subjected to Erichsen processing of 6 mm, 8 mm, and 10 mm without being cut, and then the presence or absence of cracks in the first embossed layer was observed.

[0102]

Table 2

[0103]

[0104] From the results in Table 2 above, it was confirmed that the interior film (Experimental Examples 1-10) including the substrate layer, the embossed layer, the metal layer, and the base layer according to the present invention showed excellent physical properties in all the measurement items. On the contrary, the interior film (Experimental Example 11) using polyethylene terephthalate, which is out of the scope of the present invention, as the substrate layer showed poor physical properties in all the measurement items, especially showing very poor heat resistance.

Claims

1. An interior film comprising a substrate layer, one or more embossed layers, one or more metal printing layers and a base layer, characterized in that: The substrate layer is made of a resin including polyethylene terephthalate, the longitudinal elongation of the resin is 180 to 300%, and the transverse elongation is 160 to 300%, and the surface of the substrate layer is treated with a urethane resin. The above-mentioned embossing layer is formed of an ultraviolet curable polyurethane acrylate composition. The metal printing layer is formed of a composition including a binder resin and a metal pigment. The binder resin includes one or more substances selected from the group consisting of vinyl copolymers, chlorinated polypropylene, acrylic resins, urethane resins, polyamides, nitrocellulose, and cellulose acetate butyrate. The binder resin has a glass transition temperature of 50 to 80° C. and a weight average molecular weight of 250,000 to 300,000 g / mol. The base layer is formed of a composition including a resin and a curing agent. The tensile strength of the resin constituting the above-mentioned substrate layer is 10 to 35 kgf / mm 2 , the glass transition temperature is 40 to 110 °C, The ultraviolet curable polyurethane acrylate composition forming the above-mentioned embossing layer includes urethane (meth) acrylate oligomer, (meth) acrylate monomer and photoinitiator. The urethane (meth)acrylate oligomer has a glass transition temperature of 10 to 50° C. and a weight average molecular weight of 5,000 to 20,000 g / mol. The resin constituting the base layer includes one or more resins selected from the group consisting of polyester resins, epoxy resins, polyurethane resins, polyacrylic resins and polyolefin resins, and has a weight average molecular weight of 4,000 to 10,000 g / mol, a glass transition temperature of 40 to 60° C., and a hydroxyl value of 20 to 30 mgKOH / g. The curing agent constituting the base layer includes an isocyanate compound, and the isocyanate compound has an NCO content of 10 to 30% by weight, a number average molecular weight of 500 to 1,500 g / mol, and a weight average molecular weight of 1,000 to 3,000 g / mol.